2014
DOI: 10.1155/2014/624143
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Coexpression of CD4 and CD8 in Cutaneous Lesions on Prognosis of Mycosis Fungoides: A Preliminary Study

Abstract: Background. Although techniques of immunophenotyping have been successful in characterizing the cells in the cutaneous infiltrates of mycosis fungoides little evidence suggests that variations in the phenotypic characterization correlate with prognosis. Objectives. In a preliminary prospective, single-centre, study we correlated the T-cell phenotype in cutaneous biopsies with the progression of the disease to determine whether the coexpression of CD4 and CD8 has an impact on prognosis. Methods. Skin biopsy spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…de Marchi et al showed that the coexpression of CD4 and CD8 in patients with MF is associated with a slightly lower rate of progressive disease compared with patients with conventional CD4+/CD8− phenotype. These findings raise the possibility that the coexpression of CD4 and CD8 in cutaneous lesions may confer a better prognosis in MF [ 36 ]. The lower tendency of progression of the disease in our patients with the coexpression of CD4 and CD8 might be related to the increased activity of antitumor CD8+ lymphocytes infiltrating the lesions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…de Marchi et al showed that the coexpression of CD4 and CD8 in patients with MF is associated with a slightly lower rate of progressive disease compared with patients with conventional CD4+/CD8− phenotype. These findings raise the possibility that the coexpression of CD4 and CD8 in cutaneous lesions may confer a better prognosis in MF [ 36 ]. The lower tendency of progression of the disease in our patients with the coexpression of CD4 and CD8 might be related to the increased activity of antitumor CD8+ lymphocytes infiltrating the lesions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding DP immunophenotype, De Marchi et al . reported that 33% of their 30 patients showed the coexpression of CD4 and CD8.…”
Section: Discussionmentioning
confidence: 99%
“…published a retrospective cohort of 68 patients with early‐stage MF and 10 years of follow‐up and concluded that cytotoxic phenotypes and detection of monoclonal T‐cell receptor‐c gene rearrangements in early lesions of mycosis fungoides did not have any prognostic significance. De Marchi and his group published a prospective cohort of 30 DP patients followed for 3.5 years. They concluded that the coexpression of CD4 and CD8 in cutaneous lesions is not rare and is associated with a slightly lower rate of progressive disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations